La utilización del celular como recurso didáctico en los estudiantes del primer año de bachillerato del paralelo “b” de la unidad educativa temporal Inés Cobo Donoso - Días Días, Aída Liliana (2015)
Cell phone uses for teaching and learning has encouraged students socialization and integration among classmates and teachers, providing group and individual work accepting views, opinions, building an active, participatory class and projecting interest in the knowledge, of this type of resources improve the development to students in education. The investigation guide was implemented to raise the no controlled excessive use of this tool during the school day. The research was emphasized in the proper use of the cell, to encourage teachers, students and educational community the good use of this technological resource in order to become a personal, educational benefit and social exploiting, these advantages offered by new technologies for the development of education in the classroom. The cell is a resource that will develop abilities and the end skills allowing students to increase meaningful and lasting learning that help your student, professional and even for everyday work and development stage….